Learning Assessment of Humanity Courses in Project Based Learning (PBL) - Milawati; Agus Dwi Santoso; Helmy Sahirul Alim, Helmy; Nurir Rohmah (Kirana Publisher (KNPub), 2023)
The demand for Vocational Education graduates to have the skills that are needed in the work place is a challenge for these Vocational Education institutions. Various efforts in teaching methods at Vocational Education institutions have been carried out with the intention of increasing the competitiveness of Vocational Education. Practice has the largest percentage in vocational education. Multimedia utilization; practice and work with groups; take advantage of the surrounding environment; as well as multiple aspects. One of the kinds in learning that fits with the previous explanation is the type of Project Based Learning or PBL. Learning evaluation is the process of obtaining data and information needed to determine how far and how learning has taken place in order to be able to make the necessary judgments and improvements to maximize results. The purpose of this research is to examine the needs analysis of assessment instruments in humanities courses, especially in English course. After having an attention to the stages of analysis of the questions in this study, it can be concluded that the types of assessment needed in learning evaluation activities in Project Based Learning or PBL classes are: (1) types of learning evaluation in the form of Authentic Assessments; (2) the type of learning evaluation is in the form of an Test Assessment.